IDENTIFIKASI MAKANAN YANG MENGANDUNG BORAKS DENGAN MENGGUNAKAN KUNYIT DI DESA BULUSIDOKARE, KECAMATAN SIDOARJO, KABUPATEN SIDOARJO - Medya Ayunda Fitri; Yulia Tri Rahkadima; Trisna Kumala Dhaniswara; Qurrota A’yuni; Anis Febriati (Journal of Science and Social Development, 2018)
The formation of quality human resources (HR) is influenced by many factors, one of which is about the quality of health of young people at the best level. Borax is a chemical compound derived from heavy metals boron (B). Borax is an anti-septic and bacterial killer. In Regulation of the Minister of Health No. 722 / MenKes / Per / IX / 88 borax is stated as a hazardous material and is prohibited to be used in making food. Bulusidokare Subdistrict, Sidoarjo Subdistrict, is an area that is close to learning environments such as schools and Tutoring, so that it is vulnerable to foods that contain hazardous Food Additives (FA). Therefore, it is necessary to provide counseling training to housewives about the dangers of borax to health and how to analyze the content of borax in a simple and inexpensive way. The test material used is turmeric and toothpicks. While the samples to be tested are pentol, sausage, tofu, and borax. Borax is a FA which is very dangerous for health, the highest dose limit of 10-20 gr / kg of adult bodys weight and 5 gr / kg of body weight of children will cause poisoning and even death. Food ingredients that contain borax experience discoloration on toothpicks that have been soaked in turmeric solution which is red. The method of analyzing the content of borax using turmeric is a simple and inexpensive method because it uses ingredients that are always available at home, and the method of analyzing the content of borax using turmeric can be applied to food ingredients with soft texture.